Precordial isopotential electrocardiographic mapping and its clinical use in patients with ischaemic heart disease - Janota, M; Málek, I; Stanĕk, V (Physiological research, 1993)
After ten years of experience, the authors present an overview of the possible clinical uses of precordial isopotential electrocardiographic mapping in patients with ischaemic heart disease. The resting Q wave and ST segment maps have most often been found useful in the early phases of myocardial infarction. They are a helpful tool for monitoring progression of the disease, the effect of drugs, or the therapeutic effect of fibrinolytic therapy, etc. R wave mapping provides an excellent opportunity for following up patients after orthotopic heart transplantation and monitoring cardiac rejection. Stress tests are usually performed under a workload; alternative loads may be mental, pharmacological, stimulation-induced or under hypoxaemic stress. To evaluate a test, resting values are compared with those obtained during exercise. It is mainly exercise ST segment maps which have proved to be most informative; their use in the chronic phase of ischaemic heart disease helps to make the diagnosis of coronary insufficiency more accurate. In clinical practice, stress tests are recommended mostly in the follow-up of drug therapy, monitoring of the therapeutic effect of cardiac surgery or coronary angioplasty.
Keywords: zátěžový test; psychický stres; Stress, Psychological; trombolytická terapie; Rest; Stimulation, Chemical; Thrombolytic Therapy; Exercise Test; Humans; chemická stimulace; lidé; infarkt myokardu; Myocardial Infarction; koronární nemoc; Electrocardiography; odpočinek; Coronary Disease; elektrokardiografie